Ewe-lamb bond of experienced and inexperienced mothers undernourished during gestation - Freitas-de-Melo, Aline (Sci Rep, 2021)
The aims were to compare ewe-lamb behaviours between primiparous (PRI) and multiparous (MUL) undernourished grazing ewes at birth and at 3 months of age, and to determine if mothers’ parity affects milk yield and composition, and lambs’ body weight (BW). Food availability restricted the nutritional requirements from day 30 to day 143 of gestation. The MUL ewes had greater BW than the PRI during gestation, and their lambs tended to vocalize less frequently until their first suckle. PRI ewes both displayed a lower frequency of acceptance behaviours and, a greater number of high-pitched bleats toward the alien lamb than toward that of their own, but MUL did not. PRI ewes produced less milk than the MUL ewes. The heart rate was greater in lambs reared by MUL ewes than by PRI. Although PRI ewes had a lower BW during gestation, this difference was stable throughout and did not affect the establishment of the ewe-lamb bond neither at birth nor at 3 months postpartum. At least under nutritionally restricted conditions during gestation, inexperienced mothers appeared to have had a shorter sensitivity period of maternal responsiveness than that of experienced mothers.